2017
DOI: 10.1093/jpids/pix085
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation and Weather Changes Related to the Occurrence and Severity of Acute Hematogenous Osteomyelitis in Children

Abstract: This study identified seasonal variation in the occurrence of AHO in children; summer was the most common season for occurrence. To our knowledge, this is the first detailed evaluation of weather parameters and trends in weather changes from symptom onset to admission with consideration of the effects of weather on the occurrence of infection and severity of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…Our search identified 2191 unique documents. Eighteen studies met all criteria and were included in this review . Figure represents the process of inclusion and exclusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search identified 2191 unique documents. Eighteen studies met all criteria and were included in this review . Figure represents the process of inclusion and exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…with 9128 infections . Sixteen (89%) studies directly stated the number of infection cases while case number was obtained from the authors for one manuscript (7%) and could not be derived for one study . Most research was carried out in the USA (14 studies, 78%) while one study each was conducted in Taiwan, Japan, Australia and Switzerland .…”
Section: Resultsmentioning
confidence: 99%
“…17 More recently, Lindsay et al identified that a change in average humidity between symptom onset and admission in the winter was significantly associated with severity of illness among children with haematogenous osteomyelitis in the USA. 16 These same authors conceded that the complex interaction between environment, pathogen and host made it difficult to explain this finding. A commonly proposed mechanism for the impact of weather on skin and soft tissue infection rates is that commensal organisms such as staphylococcal species proliferate at optimal moisture and temperature conditions to levels that increase the risk of infection, 7 a theory reinforced by laboratory studies.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus and coagulase-negative staphylococci are the primary infecting organisms following orthopaedic surgery and these too display seasonality based on meteorological and calendar patterns. [13][14][15] Humidity has also been implicated in the severity of acute haematogenous osteomyelitis, 16,17 suggesting that in addition to temperature other features such as moisture, rainfall and air quality also influence the pathogenicity of commensal skin flora in orthopaedic patients. [13][14][15] Humidity has also been implicated in the severity of acute haematogenous osteomyelitis, 16,17 suggesting that in addition to temperature other features such as moisture, rainfall and air quality also influence the pathogenicity of commensal skin flora in orthopaedic patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation